2001
DOI: 10.1046/j.1365-8711.2001.04064.x
|View full text |Cite
|
Sign up to set email alerts
|

Chandra High-Resolution Camera observations of the luminous X-ray source in the starburst galaxy M82

Abstract: We analyse Chandra High Resolution Camera observations of the starburst galaxy M82, concentrating on the most luminous X‐ray source. We find a position for the source of (J2000) with a 1σ radial error of 0.7 arcsec. The accurate X‐ray position shows that the luminous source is neither at the dynamical centre of M82 nor coincident with any suggested radio AGN candidate. The source is highly variable between observations, which suggests that it is a compact object and not a supernova or remnant. There is no s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
265
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 255 publications
(271 citation statements)
references
References 41 publications
(48 reference statements)
6
265
0
Order By: Relevance
“…We therefore concluded that M82 is likely to harbor an AGN, in agreement with Ptak & Griffiths (1999) and Matsumoto & Tsuru (1999). Meanwhile, subsequent observations with Chandra at about 1A spatial resolution suggest that a highly variable source about 9A o † the nucleus, which is dominating the hard X-ray Ñux, is compatible with a mid-mass black hole candidate (Kaaret et al 2001 ;Matsumoto et al 2001). If this can be proven, it would explain the location of M82 in Figure 3 since the same kind of physics is applied.…”
Section: Mirèx-ray Correlationsupporting
confidence: 64%
“…We therefore concluded that M82 is likely to harbor an AGN, in agreement with Ptak & Griffiths (1999) and Matsumoto & Tsuru (1999). Meanwhile, subsequent observations with Chandra at about 1A spatial resolution suggest that a highly variable source about 9A o † the nucleus, which is dominating the hard X-ray Ñux, is compatible with a mid-mass black hole candidate (Kaaret et al 2001 ;Matsumoto et al 2001). If this can be proven, it would explain the location of M82 in Figure 3 since the same kind of physics is applied.…”
Section: Mirèx-ray Correlationsupporting
confidence: 64%
“…Similarly, simple photon counting arguments for high-excitation optical line emission regions near ULXs make the same argument (Pakull & Mirioni 2002;Kaaret et al 2004). The source for which most evidence stacks up is M82 X-1, which through a combination of its extreme luminosity (L X,peak ∼ 10 41 erg s −1 ), co-location with the young, dense stellar cluster MGG 11, and QPO detections is the best known candidate for an IMBH (Kaaret et al 2001;Strohmayer & Mushotzky 2003;Portegies Zwart et al 2004;Mucciarelli et al 2006). However, it is possible this source is an atypical ULX; it may be the nucleus of an accreted dwarf galaxy (King & Dehnen 2005).…”
Section: A New Class Of Black Holes?mentioning
confidence: 80%
“…One pertinent finding is that starburst galaxies often contain ULXs (e.g., Kilgard et al 2002 for a minisurvey; for M82 see Matsumoto et al 2001, Kaaret et al 2001, and Griffiths et al 2000; for the Antennae [NGC 4038/39], see Fabbiano, Zezas, & Murray 2001; for the Circinus galaxy see Bauer et al 2001 andSmith &; for NGC 3256 see Lira et al 2002; and for NGC 3628 see Strickland et al 2001). This finding strongly suggests that many ULXs are associated with ongoing star formation and perhaps with massive stars.…”
Section: Introductionmentioning
confidence: 98%
“…One of the most intriguing and puzzling classes of X-ray source comprises the so-called ultraluminous X-ray sources (ULXs), whose luminosities (>10 39 ergs s À1 , sometimes greater than 10 40 ergs s À1 ) considerably exceed the Eddington luminosity of a neutron star (e.g., Fabbiano 1996;Makishima et al 2000 and references therein). An ULX may be a stellar mass black hole radiating near or above the Eddington luminosity (Begelman 2002), a stellar mass black hole or neutron star with beamed X-ray emission (Reynolds et al 1997;King et al 2001;Körding, Falcke, & Markoff 2002), or an intermediate-mass ($100 M or higher, but smaller than those in AGNs) black hole radiating near or lower than the Eddington luminosity Kaaret et al 2001). …”
Section: Introductionmentioning
confidence: 99%